Tradução e adaptação cultural da ferramenta Strongkids para triagem do risco de desnutrição em crianças hospitalizadas - Carvalho, Fernanda Christina de (2013)
Objective: To translate into Portuguese and to culturally adapt the malnutrition screening tool for hospitalized children, Strongkids. Methods: This study documents the translation of the tool from the original version (English) into Portuguese. The translation and cultural adaptation of the content of this tool consisted of six stages, according to the methodology proposed by Beaton et al (initial translation, synthesis of translations, back translation, verification of the cultural equivalence process, pre-test, and evaluation of the cultural adaptation process). In the first stage, translation was performed by two independent translators, followed by their synthesis and reconciliation; in the third one, the reconciled version was back translated and, then, a pre-final one that retained all linguistic equivalence was developed. In the fifth step, a pre-test of the pre-final version was performed in order to verify the understanding of the items and a final version of the tool was developed. Results: The pre-final version of the tool was applied to 30 parents/guardians and to 20 healthcare professionals in order to verify its understanding by both. The main alterations were the adaptation of technical terms in order to meet the recommendations of health professionals, and the adjustment of terms for parents/guardians understanding. Conclusions: The Portuguese translation of the tool was easily understood by parents/guardians and health professionals, and it should be useful to screen the risk of malnutrition in hospitalized children.